The poem that changed America : "Howl" fifty years later - Shinder, Jason, 1955-2008. (New York : Farrar, Straus and Giroux, 2006)
Reflections from America's prominent writers on the seminal poem "Howl" by Allen Ginsberg, on the eve of its fiftieth anniversary.
Wild at heart / Vivian Gornick -- Human seraphim: "howl," sex, and holiness / Mark Doty -- "Howl" and hail / Amiri Baraka -- "A lost battalion of platonic conversationalists": "Howl" and the language of modernism / Marjorie Perloff -- A witness / Bob Rosenthal -- "Howl" in Transylvania / Andrei Codrescu -- Talking Howl 1: Jack Kerouac, Louis Ginsberg, William Carlos Williams, Lawrence Ferlinghetti, M.L. Rosenthal, John Hollander, Judge Clayton Horn -- On the granite steps of the madhouse with Shaven heads / Rick Moody -- Not the, not now / Sven Birkerts -- Repeating Allen / Eileen Myles -- Wopbopgooglemop: "Howl" and its influences / Gordon Ball -- My "Howl" / Billy Collins -- The poet as Jew: "Howl" revisited / Alicia Ostriker -- A thirteen-year-old cadet / Kurt Brown -- "Howl" and me / Phillip Lopate -- Talking Howl 2: James Dickey, Kenneth Rexroth, Kenneth Patchen, Donald Justice, Richard Eberhart, Anais Nin, Reed Whittemore, Czeslaw Milosz -- I've lived with and enjoyed "Howl" / Allen Ginsberg -- The best mind / Jane Kramer -- Welcoming "Howl" into the canon / David Gates -- Writing through Howl / John Cage -- Radical eyes: political poetics and "Howl" / Eliot Katz -- The best bones for soup have meat on them / Marge Piercy -- Talking Howl 3: Paul Zweig, Lewis Hyde, Bob Dylan, Michael McCure, Vaclav Havel, Cynthia Ozick, Denise Levertov, Andy Clausen, Antler, Ann Charters, Stanley Kunitz -- The ballot of eternity / Luc Sante -- Holy the fifth international / Robert Polito -- "Howl" in and out of prison / Carol Muske-Dukes -- A cross in the void / Frank Bidart -- No picnic / Robert Pinsky -- Premises of consciousness / Anne Waldman.
Includes bibliographical references.
Keywords: Ginsberg, Allen, -- 1926-1997.; National characteristics, American, in literature; Social change -- United States -- History -- 20th century